(Nie)nowe problemy edukacji i rehabilitacji osób z niepełnosprawnościami i o zróżnicowanych potrzebach = (Not)new problems of education and rehabilitation of people with disabilities and diverse needs - Janiszewska-Nieścioruk, Zdzisława - red. nauk. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A relatively broad view of the issues of education and rehabilitation of children, adolescents and adults with disabilities and diverse needs, in the opinion of the editor of this monograph and the authors of its individual chapters, i.e. from different perspectives - researchers and practitioners, makes it possible to better understand their currently still intractable situation and experiences of disability, and in particular their place in today`s dynamically changing society (from Introduction).
Keywords: dziecko z niepełnosprawnością intelektualną; edukacja włączająca; niepełnosprawność intelektualna; rehabilitacja medyczna; uczniowie ze specjalnymi potrzebami edukacyjnymi; Polska